PENGELOLAAN SAMPAH DALAM IMPLEMENTASI SMART CITY DI KOTA BOGOR - Aniq Fajriyati Sa'diyah; Eko Priyo Purnomo; Aulia Nur Kasiwi (Jurnal Ilmu Pemerintahan Widya Praja, 2020)
The city of Bogor is one of the cities that has implemented the concept of smart city and is one of the centers of attention for the movement of people. The implementation of smart cities often has difficulty in applying various aspects. One of them is about environmental problems in urban areas that are very vulnerable to various damages such as garbage. One effort to improve the quality of the urban environment is the concept of Smart Environment. This study uses qualitative research with a descriptive approach. This research results that the condition of Bogor City which is dense makes the volume of waste increasing. In this case, waste management efforts such as the Trash Bank, 3R Trash Program, and impelemntation of waste management of IT based. However, in its application the City of Bogor experienced constraints on public awareness and participation. Keywords: Waste Management, Smart City, Smart Environment